PENGEMBANGAN MEDIA PEMBELAJARAN KIMIA BERBASIS AUTOPLAY MEDIA STUDIO 8 PADA POKOK BAHASAN STRUKTUR ATOM - ', Parsinawati; Holiwarni, Betty; ', Abdullah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Research development of chemical-based learning media Autoplay Media Studio 8 is intended to produce a decent learning media on the subject of the atomic structure is developed based on the feasibility aspect of the display media, programming, content, presentation material content and language in Chemical Education Program. Beside that, it also to know the response of chemistry teachers and learners to media-based learning Autoplay Media Studio 8 has been developed on the subject of atomic structure. This media development research using ADDIE model of which has 5 stages of development, namely analysis, design, development, implementation and evaluation. Results of research-based instructional media development AutoPlay Media Studio 8 on the subject of atomic structures that have been validated by a validator to be feasible with an average percentage of 96.38%. Response chemistry teachers and learners expressed either by the average percentage of 98.2% for chemistry teachers and 91.89% for the learners. This indicates that the learning generated media fit for use as a medium of learning.Key Words : Learning media, Autoplay Media Studio 8, Atomic Structure